2021
DOI: 10.1007/s11115-021-00532-6
|View full text |Cite
|
Sign up to set email alerts
|

Responsible Management Education in Time of Crisis: A Conceptual Framework for Public Business Schools in Egypt and Similar Middle Eastern Context

Abstract: Recent studies show that the adoption of RME scenarios is still a matter of concern for non-western countries ((Mousa et al., Journal of Management Development 38:681–696, 2019), 2021a, 2021b). In this paper, we theoretically propose the potential direction of RME scenarios that business schools in Egypt and other similar cultural context to implement through articulating the main antecedents of RME before and after Covid-19. we used the method of multilevel research by combining different theoretical approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
0
26
0
1
Order By: Relevance
“…Thereby providing reliable and trustworthy information that is needed in today's competitive business environment. The COVID-19 pandemic put management educators under stress, due to the need to provide information in a new format ( Mousa, Massoud & Ayoubi, 2022 , pp. 1–11).…”
Section: Changes In Management Education Teaching and Learning Methodsmentioning
confidence: 99%
“…Thereby providing reliable and trustworthy information that is needed in today's competitive business environment. The COVID-19 pandemic put management educators under stress, due to the need to provide information in a new format ( Mousa, Massoud & Ayoubi, 2022 , pp. 1–11).…”
Section: Changes In Management Education Teaching and Learning Methodsmentioning
confidence: 99%
“…This reduces public trust of management education and management educators (Murillo and Vallentin, 2016). However, there is a general understanding in society of the difficulty in finding an easy remedy for the problems in business schools, which, in turn, differ in their orientation (public, private), history, rank, size (number of academics and students), language of instruction, heterogeneity of academic personnel (male/female; senior/early stage), availability of funding and the cultural context in which they work (Murillo and Vallentin, 2016; Mousa et al , 2021).…”
Section: Business Schools and The Development Of Responsible Leadersmentioning
confidence: 99%
“…Other researchers (Manuel & Herron, 2020 ) investigated the ethical motivations firms used for their CSR decisions and determined that utilitarianism and deontology led to CSR activities in response to the pandemic. Lastly, in a study of Egyptian business schools, Mousa ( 2021 ) and colleagues (Mousa et al, 2021 ) concluded that business schools can implement responsible management education strategies post COVID‐19 but only after they overcome obstacles of self‐determination, contextuality, and nationalism.…”
Section: Introductionmentioning
confidence: 99%